Phospholamban R14del mutation in patients diagnosed with dilated cardiomyopathy or arrhythmogenic right ventricular cardiomyopathy: evidence supporting the concept of arrhythmogenic cardiomyopathy - van der Zwaag, Paul A. (Oxford University Press, 2012)
AIMS: To investigate whether phospholamban gene (PLN) mutations underlie patients diagnosed with either arrhythmogenic right ventricular cardiomyopathy (ARVC) or idiopathic dilated cardiomyopathy (DCM). METHODS AND RESULTS: We screened a cohort of 97 ARVC and 257 DCM unrelated index patients for PLN mutations and evaluated their clinical characteristics. PLN mutation R14del was identified in 12 (12 % ) ARVC patients and in 39 (15 % ) DCM patients. Haplotype analysis revealed a common founder, estimated to be between 575 and 825 years old. A low voltage electrocardiogram was present in 46 % of R14del carriers. Compared with R14del– DCM patients, R14del+ DCM patients more often demonstrated appropriate implantable cardioverter defibrillator discharge (47 % vs. 10 % , P < 0.001), cardiac transplantation (18 % vs. 2 % , P < 0.001), and a family history for sudden cardiac death (SCD) at < 50 years (36 % vs. 16 % , P = 0.007). We observed a similar pattern in the ARVC patients although this was not statistically significant. The average age of 26 family members who died of SCD was 37.7 years. Immunohistochemistry in available myocardial samples revealed absent/depressed plakoglobin levels at intercalated disks in five of seven (71 % ) R14del+ ARVC samples, but in only one of nine (11 % ) R14del+ DCM samples (P = 0.03). CONCLUSIONS: The PLN R14del founder mutation is present in a substantial number of patients clinically diagnosed with DCM or ARVC. R14del+ patients diagnosed with DCM showed an arrhythmogenic phenotype, and SCD at young age can be the presenting symptom. These findings support the concept of ‘arrhythmogenic cardiomyopathy’.